Dynamic analysis and driving force optimization of a 5-DOF parallel manipulator with redundant actuation. (December 2017) - Yao, Jiantao; Gu, Weidong; Feng, Zongqiang; Chen, Lipo; Xu, Yundou; Zhao, Yongsheng
Abstract: Redundant actuation can improve the performance and ability of parallel manipulator. In order to deal with coordination and distribution of the driving force of the parallel manipulator with redundant actuation and to realize the control strategy based on dynamics, on the basis of the original 5UPS/PRPU parallel manipulator, it increases a drive for the middle PRPU passive constraint branch to make it a redundant actuation branch. It introduces configurations' redundant types and compositions of 5UPS/PRPU parallel manipulator with redundant actuation, illustrates that the mechanism is redundant actuation from the perspective of degree of freedom and establishes a dynamic model based on Lagrangian method. On the basis of the weighted optimization principle of driving torque, it optimizes the driving torque of the parallel manipulator and calculates the driving force of the redundant driving chain with cutting force. It carries out the simulation by using ADAMS software and proves validity of dynamic model. Finally it detects the dynamic performance of the parallel manipulator by processing experiment of parallel manipulator with redundant actuation and its non-redundant counterpart. Highlights: We add a redundant drive to the original 5UPS/PRPU parallel manipulator. We establish the dynamic model based on Lagrange method. The weighted optimization principle of driving torque is used to optimize the driving force. By using ADAMS, it simulates the cutting process of the parallel manipulator. The dynamic performance is detected by different processing experiment.